De unione Verbi incarnati - Thomas, Aquinas, Saint, 1225?-1274. (Leuven)
xi, 157 s.
Keywords: “This volume contains the first publication in book form of an English translation of Thomas Aquinas’s controversial disputed question De unione Verbi incarnati. This disputed question is a remarkable portal into the Angelic Doctor’s theology of the hypostatic union, which is recognized as an area in which Aquinas forged some of his most original and penetrating articulations of the Christian faith. In the De unione Verbi incarnati Aquinas presents in five articles material that occupies more than eighteen questions in the third part of the Summa theologiae. The attribution of an esse secundarium to Christ, in the fourth article of the De unione, has been the object of intense debate, for it seems to contradict the account of the Summa. In addition to Professor Nutt’s English translation, the volume includes the critical Latin text published by Barbara Bartocci, Klaus Obenauer, and Walter Senner, as well as a substantial introduction. Professor Nutt’s introduction carefully unfolds the historical background, technical concepts, sources, and speculative claims needed for understanding the breadth of the biblical and metaphysical contemplation represented in this work; it also includes a detailed exploration of the debate over the fourth article.“ --